PESANTREN EDUCATION AS A STRATEGY FOR PREVENTING RADICALISM AND EXTREMISM - Ilmiyah, Khoridatul; Suharto, Babun; Syafi'i, Imam (FAJAR Jurnal Pendidikan Islam, 2026)
Pesantren are the oldest Islamic educational institutions in Indonesia and play a strategic role in shaping the religious character of students (santri). Amid the increasing phenomenon of religious radicalism and extremism, pesantren are often positioned ambivalently: on the one hand, they are accused of being fertile grounds for radicalism; on the other hand, they function as strongholds of Islamic moderation. This article aims to analyze the role of pesantren education as a strategy for preventing religious radicalism and extremism through a literature review. The study employs a library research method by examining books, reputable national and international journal articles, and policy documents relevant to pesantren, Islamic education, and deradicalization. The findings indicate that pesantren education contributes significantly to preventing radicalism through the internalization of religious moderation values, the strengthening of kiai’s scholarly authority, the preservation of classical Islamic scholarly traditions (turath), and pesantren culture that emphasizes the principles of tawassuth (moderation), tasamuh (tolerance), tawazun (balance), and i‘tidal (justice). Pesantren also play a role in building the ideological resilience of santri so that they are not easily exposed to extremist religious ideologies. This article recommends strengthening pesantren curricula based on religious moderation and enhancing students’ digital literacy as preventive measures against radicalism in the digital era